Relationship between severity of the local skin reactions and the rate of local skin reaction resolution in patients treated with ingenol mebutate gel - Jim On SC; Knudsen KM; Skov T; Lebwohl M (Dove Medical Press, 2016)
Shelbi C Jim On,1 Kim Mark Knudsen,2 Torsten Skov,2 Mark Lebwohl,1 1Department of Dermatology, Mount Sinai School of Medicine, New York, NY, USA; 2LEO Pharma A/S, Biostatistics, Ballerup, Denmark Background: Ingenol mebutate gel is a topical field treatment for actinic keratosis (AK). The treatment elicits application-site reactions in most patients. This analysis evaluated the relationship between the severity of reactions and the speed of their resolution.  Methods: Patients in Phase III studies were treated for AKs on the face (n=218), scalp (n=56), and trunk and extremities (n=209). All of the patients were treated with either ingenol mebutate gel 0.015% once daily for three consecutive days (face/scalp) or ingenol mebutate gel 0.05% once daily for two consecutive days (trunk/extremities). Local skin reactions (LSRs) were assessed on a 5-point scale from 0 to 4 in six categories, yielding composite scores in the range of 0 to 24. Results: The composite LSR score on the day after the last application of ingenol mebutate gel was an important predictor of the speed of resolution of LSRs. The rate of resolution was greatest for AKs treated on the face, followed by the scalp, and then the trunk and extremities. All patients were expected to have minimal LSR scores for the face and scalp at 2 weeks, and for the trunk and extremities at 4 weeks. Conclusion: The absolute reduction in LSR scores was proportional to the composite LSR score on the day after the last application of ingenol mebutate gel treatment. The rate of resolution for LSRs was dependent on the anatomic site treated as well as the day 4 composite score. Keywords: ingenol mebutate, local skin reaction, actinic keratosis